Development and characterization of edible chitosan/olive oil emulsion films - Pereda, Mariana (2012)
The properties of plasticized chitosan-olive oil emulsion films prepared with increasing oil concentrations were investigated. Emulsifying nature of chitosan was enough to stabilize olive oil droplets in the film forming emulsions; hence homogeneous, thin and translucent films were obtained in all cases. The homogeneity of the lipid globules distribution in the films was confirmed by contact angle measurements and optical microscopy. All the tensile properties (Young Modulus, strength and maximum elongation) increased with olive oil concentration and were explained considering the interactions developed between lipid and carbohydrate phases in addition to the lubricant characteristics of the oil. Moisture sorption, water vapor permeation through the films and effective diffusion coefficients decreased as oil concentration increases, as a result of the non-polar nature of the lipid. Total soluble matter measurements were used to confirm the development of strong associations between chitosan and olive oil. © 2011 Elsevier Ltd. All rights reserved.